Determination of physical and mechanical properties of carrot (Daucus carota) for designing combine harvesting mechanism - NATH, SHYAM; KUMAR, ADARSH; MANI, INDRA; SINGH, JAI KUMAR; SUREJA, AMISH KUMAR (The Indian Journal of Agricultural Sciences, 2019)
The main objective of this study was to measure the properties of the carrot to design carrot (Daucus carota L.) harvesting mechanism. Physical properties were beneficial to fix the relative position of carrot harvesting mechanism and mechanical properties were helping in functionality of the carrot combine harvester mechanism. Three carrot cultivars namely Pusa Keshar, Pusa Rudhira and Nantes cultivar were taken for the study. Length of carrot, effective foliage length (stem node), carrot head (crown) above soil surface; weight and upper root diameter were included in physical properties measurement. Pulling and tensile force were included in mechanical properties measurement. The foliage length was found in the range from 46 to 90cm, however, the crown height was observed at 1.5 cm above the soil surface. Carrot root length of Pusa Keshar, Pusa Rudhira and Nantes were 23.10 ± 3.71, 21.68 ± 4.14 and 18.64 ± 3.49 cm, respectively. Average pulling force in undisturbed (unloosen) raised bed highest was observed with Pusa Rudhira (148.93 ± 73.46 N) followed by Pusa Keshar (133.10 ± 62.15) and Nantes (118.18 ± 41.72). While, the pulling force for loosen raised bed were observed in following order Pusa Rudhira (22.41 ± 7.64 N) >Pusa Keshar (21.35 ± 5.84 N) >Nantes (20.21 ± 5.52 N). The loosen soil imposed 5 to 6 time lesser resistance on pulling carrot than unloosen raised bed. Average foliage detachment force (tensile force) from carrot crown was 236.13 ± 20.66, 211.95 ± 16.81 and 243.35 ± 47.73 N for Pusa Keshar, Nantes and Pusa Rudhira, respectively. It was observed that pulling force in loose raised bed was around 10 times lesser than the foliage detachment force.